2020
DOI: 10.1038/s41598-020-64133-x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of cytomegalovirus (CMV)-specific cell-mediated immune response using QuantiFERON-CMV assay in CMV-seropositive healthy volunteers: fact not artifact

Abstract: The QuantiFERON-CMV (QF) assay measures cell-mediated immunity against cytomegalovirus (CMV-CMI), which is particularly useful in individuals susceptible to CMV infection such as transplant patients. A positive QF result identifies patients that are better protected against CMV infection. However, the significance of a negative QF result in CMV-seropositive individuals needs to be clarified. CMV-CMI was analyzed in healthy subjects using the QF assay, and, in parallel, the Flow-cytometric Assay of Specific Cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…About 60% of pretransplant CMV-seropositive recipients were negative for CMV-QF [ 70 ]. A recent study performed CMV-CMI in healthy individuals and found 18.3% (13/71) revealed humoral/cellular discordance, showing CMV-seropositivity with CMV-QF negativity [ 71 ]. Individuals with inconsistent results had lower levels of CD4+ and CD8+ T cell proliferation in response to CMV lysate stimulation and expressed a lower level of anti-CMV IgG.…”
Section: Assays For Immune Responses After CMV Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…About 60% of pretransplant CMV-seropositive recipients were negative for CMV-QF [ 70 ]. A recent study performed CMV-CMI in healthy individuals and found 18.3% (13/71) revealed humoral/cellular discordance, showing CMV-seropositivity with CMV-QF negativity [ 71 ]. Individuals with inconsistent results had lower levels of CD4+ and CD8+ T cell proliferation in response to CMV lysate stimulation and expressed a lower level of anti-CMV IgG.…”
Section: Assays For Immune Responses After CMV Infectionmentioning
confidence: 99%
“…Individuals with inconsistent results had lower levels of CD4+ and CD8+ T cell proliferation in response to CMV lysate stimulation and expressed a lower level of anti-CMV IgG. This suggests that immune response to CMV was highly heterogeneous in healthy subjects [ 71 ]. In addition, CMV-QF only measures the CMV-specific CD8+ T cell response.…”
Section: Assays For Immune Responses After CMV Infectionmentioning
confidence: 99%
“…The study by Zhang et al raises the possibility that sFasL may contribute to host defenses by aiding the resolution of inflammatory exudate, independently of any effect on viral replication [33]. The lack of CMV-specific cell-mediated immune response detected by QuantiFERON-CMV assay in CMV-seropositive individuals was already reported by Valle-Arroyo et al [29] CMV infection can change the expression of NK cell membrane receptors, promoting the progressive expansion and persistence of mature phenotypes characterized by CD56 dim , KIR expression and NKG2A neg /CD57 pos . Our results are intriguing, because double-positive cells are NK cell subsets characterized by the double expression of NKG2A and KIR.…”
Section: Discussionmentioning
confidence: 78%
“…Let us also highlight a possible bias of our study due to QF-CMV. This in vitro assay measures CMV cell-mediated immunity by quantifying INFγ released by cells after stimulation with a pool of HLA-restricted CMV peptides [ 29 ]. Many limits of this method have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…These data could identify individuals at higher risk of infection (eg, patients who have positive CMV IgG but are QF-nonreactive). The high heterogeneity of CMV-specific immunity has also been demonstrated in immunocompetent individuals [ 27 ].…”
Section: Discussionmentioning
confidence: 99%